Binary Homodyne Detection for Observing Quadrature Squeezing in Satellite Links - Müller, Christian R.; Seshadreesan, Kaushik P.; Peuntinger, Christian; Marquardt, Christoph (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
Optical satellite links open up new prospects for realizing quantum physical experiments over unprecedented length scales. We demonstrate the feasibility of quadrature squeezing detection in satellite links using optical communication technology already in orbit. The detection process is complicated by the fact that the homo dyne detectors aboard of satellites often provide an efficient resolution of only one bit. We show experimentally, that despite this extremal constraint quantum squeezing can still be detected efficiently. The required sample overhead compared to an ideal homo dyne detector is only a factor of 3.3.
CRIS-Team Scopus Importer:2019-05-21

Binary homodyne detection for observing quadrature squeezing in satellite links - Müller, Christian; Seshadreesan, Kaushik P.; Peuntinger, Christian; Marquardt, Christoph (Physical Review Research, 2020)
Optical satellite links open up new prospects for realizing quantum physical experiments over unprecedented length scales. We analyze and affirm the feasibility of detecting quantum squeezing in an optical mode with homodyne detection of only one bit resolution, as is found in satellites already in orbit. We show experimentally that, in combination with a coherent displacement, a binary homodyne detector can still detect quantum squeezing efficiently even under high loss. The sample overhead in comparison to nondiscretized homodyne detection is merely a factor of 3.3.
CRIS-Team WoS Importer:2021-01-22

Fading channel estimation for free-space continuous-variable secure quantum communication - Ruppert, Laszlo; Peuntinger, Christian; Heim, Bettina; Günthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique Alexander; Leuchs, Gerd; Filip, Radim; Marquardt, Christoph (New Journal of Physics, 2019)
We investigate estimation of fluctuating channels and its effect on security of continuous-variable quantum key distribution. We propose a novel estimation scheme which is based on the clusterization of the estimated transmittance data. We show that uncertainty about whether the transmittance is fixed or not results in a lower key rate. However, if the total number of measurements is large, one can obtain using our method a key rate similar to the non-fluctuating channel even for highly fluctuating channels. We also verify our theoretical assumptions using experimental data from an atmospheric quantum channel. Our method is therefore promising for secure quantum communication over strongly fluctuating turbulent atmospheric channels.
CRIS-Team WoS Importer:2020-03-06

Free-space propagation of high-dimensional structured optical fields in an urban environment - Lavery, Martin P. J.; Peuntinger, Christian; Günthner, Kevin; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Science Advances, 2017)
Spatially structured optical fields have been used to enhance the functionality of a wide variety of systems that use light for sensing or information transfer. As higher-dimensional modes become a solution of choice in optical systems, it is important to develop channel models that suitably predict the effect of atmospheric turbulence on these modes. We investigate the propagation of a set of orthogonal spatial modes across a free-space channel between two buildings separated by 1.6 km. Given the circular geometry of a common optical lens, the orthogonal mode set we choose to implement is that described by the Laguerre-Gaussian (LG) field equations. Our study focuses on the preservation of phase purity, which is vital for spatial multiplexing and any system requiring full quantum-state tomography. We present experimental data for the modal degradation in a real urban environment and draw a comparison to recognized theoretical predictions of the link. Our findings indicate that adaptations to channel models are required to simulate the effects of atmospheric turbulence placed on high-dimensional structured modes that propagate over a long distance. Our study indicates that with mitigation of vortex splitting, potentially through precorrection techniques, one could overcome the challenges in a real point-to-point free-space channel in an urban environment.
CRIS-Team Scopus Importer:2022-06-05

Long distance free-space propagation of light carrying orbital angular momentum - Lavery, Martin P.J.; Peuntinger, Christian; Günthner, Kevin; Bauer, Thomas; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2016)
We present analysis of the technical challenges facing deployment of longdistance free-space links employing orbital angular momentum multiplexing. Our analysis indicates atmospheric mitigation techniques, and modal purity are important consideration for system design.
CRIS-Team Scopus Importer:2022-06-05

Proof-of-principle test of coherent-state continuous variable quantum key distribution through turbulent atmosphere - Derkach, Ivan; Peuntinger, Christian; Ruppert, Laszlo; Heim, Bettina; Gunthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd (SPIE Security + Defence, 2016)
Continuous-variable quantum key distribution is a practical application of quantum information theory that is aimed at generation of secret cryptographic key between two remote trusted parties and that uses multi-photon quantum states as carriers of key bits. Remote parties share the secret key via a quantum channel, that presumably is under control of of an eavesdropper, and which properties must be taken into account in the security analysis. Well-studied fiber-optical quantum channels commonly possess stable transmittance and low noise levels, while free-space channels represent a simpler, less demanding and more flexible alternative, but suffer from atmospheric effects such as turbulence that in particular causes a non-uniform transmittance distribution referred to as fading. Nonetheless free-space channels, providing an unobstructed line-of-sight, are more apt for short, mid-range and potentially long-range (using satellites) communication and will play an important role in the future development and implementation of QKD networks. It was previously theoretically shown that coherent-state CV QKD should be in principle possible to implement over a free-space fading channel, but strong transmittance fluctuations result in the significant modulation-dependent channel excess noise. In this regime the post-selection of highly transmitting sub-channels may be needed, which can even restore the security of the protocol in the strongly turbulent channels. We now report the first proof-of-principle experimental test of coherent state CV QKD protocol using different levels Gaussian modulation over a mid-range (1.6-kilometer long) free-space atmospheric quantum channel. The transmittance of the link was characterized using intensity measurements for the reference but channel estimation using the modulated coherent states was also studied. We consider security against Gaussian collective attacks, that were shown to be optimal against CV QKD protocols . We assumed a general entangling cloner collective attack (modeled using data obtained from the state measurement results on both trusted sides of the protocol), that allows to purify the noise added in the quantum channel . Our security analysis of coherent-state protocol also took into account the effect of imperfect channel estimation, limited post-processing efficiency and finite data ensemble size on the performance of the protocol. In this regime we observe the positive key rate even without the need of applying post-selection. We show the positive improvement of the key rate with increase of the modulation variance, still remaining low enough to tolerate the transmittance fluctuations. The obtained results show that coherent-state CV QKD protocol that uses real free-space atmospheric channel can withstand negative influence of transmittance fluctuations, limited post-processing efficiency, imperfect channel estimation and other finite-size effects, and be successfully implemented. Our result paves the way to the full-scale implementation of the CV QKD in real free-space channels at mid-range distances.<br